Empirical Analysis of Macroeconomic Determinants of Stock Market Performance: Evidence from the Nepal Stock Exchange using an ARDL Model - Thapa, Krishna Bahadur; Chamlagain, Ganga Prasad (Dristikon: A Multidisciplinary Journal, 2025)
The objective of this research is to assess the empirical analysis of macroeconomic factors with the stock market performance. This study employs an Auto-Regressive Distributed Lag (ARDL) model to analyze the determinants of the Nepal Stock Exchange (NEPSE) index from September 2012 to June 2024, utilizing 139 observations with a maximum of four lags. The study includes NEPSE as the dependent variable and key macroeconomic indicators, including lending interest rates (LIR), consumer price index (CPI), and 91-day Treasury bill rates (TB91), as explanatory variables. The optimal model, ARDL (1, 1, 0, 1), is selected based on the Akaike Information Criterion (AIC). The results reveal a strong persistence in the NEPSE index, as evidenced by the significant coefficient of the lagged dependent variable (NEPSE (-1) = 0.97, p < 0.01), indicating that past values significantly influence current values. Lending interest rates exhibit a dynamic effect, with a negative immediate impact (-148.42, p < 0.01) and a positive lagged effect (124.38, p < 0.01), reflecting short-term challenges and long-term adjustments. CPI shows a negative but statistically insignificant relationship with NEPSE (-3.74, p = 0.51), suggesting minimal direct influence. TB91 demonstrates mixed effects, with an immediate negative impact (-14.39) and a lagged positive effect (16.26), both statistically insignificant. The model exhibits strong explanatory power, with an R-squared value of 0.96 and an F-statistic (592.88, p < 0.01), confirming overall significance. The Durbin-Watson statistic (2.00) indicates no significant autocorrelation.